Most daunting aspect of being a house officer: a survey among medical graduates in a Malaysian Public University - Abdul Rashid, Aneesa (International Journal of Human and Health Sciences (IJHHS), 2023)
Objectives: Medical graduates often express their unreadiness to work due to several factors. It is important for medical educators to take steps toward assisting house officers (HO) to become work ready. This study assessed the most daunting aspects of being a HO as perceived by medical graduates in a public Malaysian university.